Islamic higher education students’ expenditure before and during pandemic in Indonesia - Ahmad Juhaidi; Ahmad Salabi; Noor Hidayati (Intelektual Pustaka Media Utama, 2022)
Students are experiencing difficulty with online learning because it requires infrastructure, such as internet access that needs to be purchased. This study examined whether online lectures increase or decrease family/student expenses on education using a qualitative approach. Data on education expenditures were collected by interviewing 736 students at State Islamic University (UIN) Antasari, Indonesia before the COVID-19 pandemic and 761 students during the occurrence. Also, interviews were used to collect data on opportunity costs during the pandemic. The results showed that the student/family average expenditure on education at State Islamic University in Indonesia (PTKIN) before the occurrence was IDR 20,420,708 per year. Meanwhile, during the pandemic, their expenses decreased to an average of IDR 15,788,989 per year, indicating a decline of IDR 4,631,719 or 22.68%.